Memorial to the Right Honourable Neville Chamberlain, M.P., Minister of Health (1925)
1925 1925 1920s 2 pages PRINTED MATTER Miss MAY YATES, Hon. Secretary, Bread and Food Reform League, 37, ESSEX STREET, LONDON, W.C.2. 292/840/1/18